1992
DOI: 10.1007/bf01741792
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional analysis of lymphocytes infiltrating paediatric tumours, with a characterization of the tumour phenotype

Abstract: Tumour-infiltrating lymphocytes (TIL) of paediatric tumours obtained from 37 lesions of different histotype (12 osteosarcomas, 5 Wilms' tumours, 7 soft-tissue sarcomas, 5 neuroblastomas and 8 miscellaneous) were studied to establish their potential for therapy. Fresh isolated TIL were cultured for the first 2 weeks with low doses of interleukin-2 (IL-2) (20 Cetus U/ml) to select for "tumour-specific" lymphocytes potentially present in the neoplastic lesion, followed by culture with high doses of IL-2 (1000 Cet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Clonal analysis showed that the majority of lymphocytes in neuroblastomas were CD3-positive T cells; in addition, of 90 neuroblastoma-derived clones, only three represented NK cells (11). Infiltrating T cells in pediatric cancers are infrequent, difficult to clone, and functionally ineffective (14). We are not aware of a previous study documenting the presence or absence of dendritic cells among the TALs in pediatric cancers, or whether that finding has any association with prognosis.…”
Section: Discussionmentioning
confidence: 84%
“…Clonal analysis showed that the majority of lymphocytes in neuroblastomas were CD3-positive T cells; in addition, of 90 neuroblastoma-derived clones, only three represented NK cells (11). Infiltrating T cells in pediatric cancers are infrequent, difficult to clone, and functionally ineffective (14). We are not aware of a previous study documenting the presence or absence of dendritic cells among the TALs in pediatric cancers, or whether that finding has any association with prognosis.…”
Section: Discussionmentioning
confidence: 84%
“…Rivoltini et al [39] found that although there was a predominance of γδ T cells in TIL from patients with osteosarcoma, TIL obtained from osteosarcoma was difficult to expand at levels required for immunotherapy, owing to a low expression of immunomodulatory molecules on tumor cells or the production of suppressive factors in paediatric tumors. In recent years, γδ T cells derived from human peripheral blood, which can be activated by phospho-antigens and aminobisphosphonates such as Zol to achieve reliably large-scale expansion in vitro, started to emerge as a rewarding target for immunotherapeutic strategies against cancer [14].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, their reduced response in the tumor tissue may be due to the suppressive influence under the tumor microenvironment. In this context, TIL have been identified in numerous neoplasia, such as melanoma [5-9], various carcinomas [10-17], myeloma [18], pediatric tumors [19] and sarcomas [20-22] and the therapeutic relevance of these TIL has been also documented in both animal models and clinical trials [23-28]. Unfortunatly, up to date, very few data is available on the phenotypic and functional characterization of TIL isolated from adult bone-associated tumors.…”
Section: Introductionmentioning
confidence: 99%